Optimalisasi Isi Situs Informasi Magister Komunikasi Penyiaran Islam Universitas Islam Negeri Sumatera Utara Medan - Indra, Farhan; Ritonga, Hasnun Jauhari; Hasibuan, Wildan Ansori; Siregar, Alya Rahmayani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to determine the strengthening of the content of the Islamic Broadcasting Communication Master's Study website, North Sumatra State Islamic University, Medan. This research uses a descriptive qualitative approach. Data sources for this research include primary data in the form of interviews, observations, and secondary data in the form of documentary studies through literature reviews. Data collection was carried out through structured interviews, observation, and documentation. This research data analysis was carried out by reducing the data, presenting it, and verifying the data. The validity of the data was tested through triangulation techniques. The results of this research show that the content on the website of the Islamic Broadcasting Communication Master's Study Program at UIN North Sumatra Medan is very important to support a targeted and efficient user experience, as well as to promote the study program through marketing and branding strategies. Strengthening content faces obstacles such as limited resources, technological challenges, and lack of involvement of lecturers and students. To overcome this, strategies such as leveraging open source, ongoing training, participation incentives, systematic evaluation, automatic content updates, and accessibility optimization are needed. By applying multimedia theory and the latest technology, study programs can increase attractiveness, provide relevant information, and build a strong reputation at national and international levels.